1992
DOI: 10.1007/bf02311851
|View full text |Cite
|
Sign up to set email alerts
|

Die transversale Dehnung mit Plattenapparaturen-intermolare Stabilität und Bedeutung für gingivale Rezessionen

Abstract: This study was undertaken to investigate if transversal expansion with removable plates is a predisposing factor in the occurrence for buccal recessions in the molar region. In order to clarify a possible causal relationship, it is important to know to what extent the therapeutic expansion remains stable, 58 former patients, ages ten to 15, were studied following transversal expansion and non-extraction therapy with removable appliances. Intermolar expansion and stability, clinical crown length, and the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…Greater therapeutic effects with relatively minor relapse were reported in the studies by Gardener & Chaconas [4] and by Nanda & Kim [17]. The present study confirms the finding of Kahl-Nieke et al [11] and of Göz et al [6] that relatively stable, moderate expansion can be achieved in the molar region. Numerous other authors reported severe relapses after larger therapeutic movements.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Greater therapeutic effects with relatively minor relapse were reported in the studies by Gardener & Chaconas [4] and by Nanda & Kim [17]. The present study confirms the finding of Kahl-Nieke et al [11] and of Göz et al [6] that relatively stable, moderate expansion can be achieved in the molar region. Numerous other authors reported severe relapses after larger therapeutic movements.…”
supporting
confidence: 82%
“…Größere Therapieeffekte mit relativ geringen Rezidiven ergaben sich bei den Untersuchungen von Gardener & Chaconas [4] sowie Nanda & Kim [17]. Im Molarenbereich konnte eine relativ stabile, moderate Erweiterung von uns, Kahl-Nieke et al [11] und Göz et al [6] festgestellt werden. Bei zahlreichen anderen Autoren folgten größeren therapeutischen Bewegungen stärkere Rezidiventwicklungen.…”
unclassified
“…The measured mean value of the gap width in the upper jaw after transverse expansion at the end of the therapy period (4.0 mm, SD 1.2) corresponded to the following published values for transverse expansion (with the reminder that these were only measured on plaster models after the end of treatment! ): 2.9 mm (SD 1.68) [3], 3 mm [8], 3.01 mm (SD 1.82) [5], 3.5 (SD 1.54) [14], 3.9 mm (SD 2.1) [4], and 4.62 (SD 1.16) [19]. The recently published high value of 6.18 mm (SD 1.82) [18] was obtained by measuring three-dimensional (3D) X-ray images and differs greatly from all other published data.…”
Section: Resultsmentioning
confidence: 99%
“…Heute nimmt die Gaumennahterweiterung im Kindesalter einen immer größer werdenden Raum ein [17]. Ursachen hierfür sind in Studien zu sehen, die den Verlust von rein dento-alveolär angestrebten "Dehnungen" nach primär erreichten transversalen Erweiterungen der Zahnbögen untersuchten [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Da in den letzten Jahren jedoch verstärkt rein dento-alveoläre Expansionen von Zahnbögen [32,33] zur Vermeidung einer primär indizierten Extraktion bleibender Zähne durchgeführt werden, um dem Patientenwunsch nach einer "minimal-invasiven" Therapie gerecht zu werden [34], stellt sich mit besonderem Nachdruck die Frage der langfristigen Stabilität eines derart erzielten Behandlungsergebnisses.…”
Section: Einführungunclassified